Aromatase Inhibitor Associated Musculoskeletal Symptoms are associated with Reduced Physical Activity among Breast Cancer Survivors. Issue 1 (25th October 2013) - Brown, Justin C.; Mao, Jun J.; Stricker, Carrie; Hwang, Wei‐Ting; Tan, Kay‐See; Schmitz, Kathryn H.
Abstract Physical activity (PA) has numerous health benefits for breast cancer survivors. Recent data suggest that some breast cancer survivors treated with aromatase inhibitors may experience aromatase inhibitor associated musculoskeletal symptoms. It is unknown whether aromatase inhibitor associated musculoskeletal symptoms are associated with reduced PA and what other risk factors are associated with such PA reductions. We conducted a cross‐sectional study at a large university‐based breast cancer clinic among breast cancer survivors prescribed an aromatase inhibitor. At routine follow‐up, we surveyed participants about aromatase inhibitor associated musculoskeletal symptoms, as well as pre‐aromatase inhibitor, and current, PA levels. Among 300 participants, 90 (30%) reported a reduction of PA since the initiation of aromatase inhibitor therapy. Those with aromatase inhibitor associated musculoskeletal symptoms were more likely to report decreased PA (62% versus 38%, p = 0.001) compared with those without aromatase inhibitor associated musculoskeletal symptoms. In multivariate analyses, aromatase inhibitor associated musculoskeletal symptoms (odds ratio [OR] = 2.29 [95% confidence interval [CI]: 1.36–3.86]), and body mass index (OR = 1.06 [95% CI: 1.02–1.12]) were associated with reductions in PA. In subgroup analysis among breast cancer survivors with aromatase inhibitor associated musculoskeletal symptoms, self‐reported lower extremity joint pain (OR = 1.23 [95% CI: 1.00–1.50]) and impaired lower extremity physical function (OR = 1.07 [95% CI: 1.01–1.14]) were associated with reductions in PA. Breast cancer survivors with aromatase inhibitor associated musculoskeletal symptoms were more likely to report reductions in PA since initiating aromatase inhibitor therapy compared with those without aromatase inhibitor associated musculoskeletal symptoms. Our findings suggest that tailored interventions targeting lower extremity functional limitations are needed to enable breast cancer survivors with aromatase inhibitor associated musculoskeletal symptoms to participate in PA.